(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2015)
Introduction: The modern high-resolution imaging has been used as a well described aid in the setting of post-mortem investigations. In developed countries Computed Tomography (CT) and Magnetic Resonance Imaging (MRI) are now being evaluated as complementary means for cause-of-death determination. Objective: This paper explores the implication of virtual autopsy from ethical and technical point of view. Methods: Published literature with strict inclusion and exclusion criteria were extensively reviewed through use of general and Meta search engines to elucidate the applications and implications of virtual autopsy. Discussion: Virtual autopsy introduces a new era in autopsy examination. It utilizes the technological innovation of modern imaging system to obtain high quality 3 Dimensional images of the body in multiple plains without mutilation of the human body. The Virtual Autopsy can be applied in a broad number of forensic situations, such as thanatological investigations; carbonized and putrefied body identifications; mass disaster cases; age estimation; anthropological examinations and skin lesion analyses, determining cause of death determination; decedent gender, identification in 001 JAFMC Bangladesh. Vol 9, No 2 (December) 2013 difficult forensic cases; body length and Individual decedent feature identification; identifying distinct foreign bodies retained bullets, blades, etc.; identification of injuries and forensic reconstructions three dimensional reconstructions, bullet tract identification; education and clinical performance improvement process; and research. Conclusion: Due to its minimal invasive procedure, virtual autopsy is very much acceptable to the society. In USA and European countries virtual autopsy is likely to replace conventional autopsies in future. We can also utilize this modern technology to upgrade the century old investigation system in our country. DOI: http://dx.doi.org/10.3329/jafmc.v9i2.21848 Journal of Armed Forces Medical College Bangladesh Vol.9(2) 2013